2010
DOI: 10.1124/mol.109.062729
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulation of Human CYP2J2 in HepG2 Cells by Butylated Hydroxyanisole Is Mediated by c-Jun and Nrf2

Abstract: Cytochrome P450 2J2 oxidizes arachidonic acid to a series of epoxyeicosatrienoic acid (EET) isomers in human tissues. EETs regulate numerous homeostatic processes, including cytoprotective and proliferative responses against injurious stresses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 34 publications
(52 reference statements)
1
18
1
Order By: Relevance
“…1A). The isothiocyanate, SFN, is believed to be a classic activator of only Nrf2 (Nguyen et al, 2009;Ahn et al, 2010), whereas BHA and acrolein modulate gene expression by activation of either Nrf2 or AP-1 (Choi and Moore, 1993;Lee and Murray, 2010). As anticipated, HO-1 (Ϸ5-fold) and NQO-1 (Ϸ3-fold) mRNA levels were significantly induced by SFN, but no significant induction of Aldh1a1 gene expression was observed with SFN ( Fig.…”
Section: Methodssupporting
confidence: 49%
See 1 more Smart Citation
“…1A). The isothiocyanate, SFN, is believed to be a classic activator of only Nrf2 (Nguyen et al, 2009;Ahn et al, 2010), whereas BHA and acrolein modulate gene expression by activation of either Nrf2 or AP-1 (Choi and Moore, 1993;Lee and Murray, 2010). As anticipated, HO-1 (Ϸ5-fold) and NQO-1 (Ϸ3-fold) mRNA levels were significantly induced by SFN, but no significant induction of Aldh1a1 gene expression was observed with SFN ( Fig.…”
Section: Methodssupporting
confidence: 49%
“…Previous studies showed that Nrf2 induces the expression of cytoprotective genes by forming active heterodimers with AP-1 proteins, in particular c-Jun (Lee and Murray, 2010). We examined whether there is cross-talk between c-Jun and Nrf2 in Aldh1a1 transcriptional activation.…”
Section: Constitutivementioning
confidence: 99%
“…Concerning the role of Nrf2 in the regulation of P450, mouse Cyp2a5 was the first reported case [12]. In addition, a recent study demonstrated that human CYP2J2 is regulated by Nrf2 [21]. We could provide evidence to put CYP2A6 into the short list of P450s that are regulated by Nrf2.…”
Section: Discussionmentioning
confidence: 88%
“…It is important to note that Lee and Murray (2010) induced their cells with BHA for 72 hours compared with the 48 hours of this study. Further, they replenished the BHA in their cell media frequently during their induction (at 6, 12, 18, 24, and 48 hours), whereas BHA was replenished at 24 hours in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A 48-hour induction period was chosen after preliminary studies indicated that significant cell death occurred at 72 hours. Lee and Murray (2010) reported BHA as a CYP2J2 inducer in HepG2 cells. Further work by Ma et al (2004) has shown that the mouse ortholog CYP2J5 is regulated by sex hormones in murine kidneys.…”
Section: Discussionmentioning
confidence: 99%